The Role of Fintech in Enhancing Financial Inclusion in Emerging Economies - Singh, Madan Kumar (Journal of Nepal Commerce Association, 2025)
The purpose of this research is to investigate the role of financial technology (Fintech) in promoting financial inclusion in emerging economies, focusing on how innovative digital solutions can address the financial access gap. The study employs a secondary data methodology, drawing insights from scholarly articles, industry reports, and case studies to assess the impact of Fintech services such as mobile banking, digital payments, and online lending platforms. Findings reveal that Fintech has significantly enhanced. Financial inclusion by providing accessible, affordable, and efficient. Financial services to previously underserved populations, including rural communities and women. However, the study also identifies challenges, including regulatory constraints, limited technological infrastructure, and socio-economic barriers that hinder the full potential of Fintech. Practical implications include the need for supportive regulatory frameworks, public-private partnerships, and targeted initiatives to overcome these challenges. This research contributes to the existing literature by providing a comprehensive analysis of the transformative role of Fintech in financial inclusion, highlighting its value in driving economic growth and reducing poverty.